1999
DOI: 10.1021/ja990034a
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Deficient Early−Late Heterobimetallic Sulfido Clusters. Unusual Reactivities of Ti2Ru2S4 Cubane-Type Clusters with Four Cyclopentadienyl Coligands

Abstract: Treatment of [Cp2Ti(SH)2] (1; Cp = η5-C5H5) with [(Cp*Ru)4(μ3-Cl)4] (2; Cp* = η5-C5Me5) in a Ti:Ru ratio of 1:1 afforded the hydrosulfido-bridged titanium−ruthenium heterobimetallic complex [Cp2Ti(μ2-SH)2RuClCp*] (3). Complex 3 reacted with an excess of triethylamine to give the early−late heterobimetallic cubane-type sulfido cluster [(CpTi)2(Cp*Ru)2(μ3-S)4] (4), with a loss of HCl and cyclopentadiene. An X-ray diffraction study and extended Hückel molecular orbital calculations for the 60e- cluster 4 demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Our recent studies toward this direction have revealed that hydrosulfido-bridged dinuclear complexes such as [Cp*MCl(μ-SH) 2 MCp*Cl] (M = Ru, Rh, Ir; Cp* = η 5 -C 5 Me 5 ) and [Cp 2 Ti(μ-SH) 2 RuCp*Cl] (Cp = η 5 -C 5 H 5 ) serve as versatile precursors for preparing the homo- and heterobimetallic cubane-type clusters such as [(Cp*M) 4 (μ 3 -S) 4 ] (M = Ru, Rh, Ir), [(CpTi) 2 (Cp*Ru) 2 (μ 3 -S) 4 ], and [CpTi(Cp*Ru) 3 (μ 3 -S) 4 ] through a dehydrochlorination−dimerization process (Scheme ). In addition, it has also been found that the Ir−Mo cluster [(Cp*Ir) 2 {Mo(O)Cl 2 }{MoCl 2 (DMF)}(μ 3 -S) 4 ] can be obtained from [Cp*IrCl(μ-SH) 2 IrCp*Cl] and [MoO(DMF) 3 (μ-S) 2 MoO(DMF) 3 ] 2+ through condensation and concomitant dehydration, which is also shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies toward this direction have revealed that hydrosulfido-bridged dinuclear complexes such as [Cp*MCl(μ-SH) 2 MCp*Cl] (M = Ru, Rh, Ir; Cp* = η 5 -C 5 Me 5 ) and [Cp 2 Ti(μ-SH) 2 RuCp*Cl] (Cp = η 5 -C 5 H 5 ) serve as versatile precursors for preparing the homo- and heterobimetallic cubane-type clusters such as [(Cp*M) 4 (μ 3 -S) 4 ] (M = Ru, Rh, Ir), [(CpTi) 2 (Cp*Ru) 2 (μ 3 -S) 4 ], and [CpTi(Cp*Ru) 3 (μ 3 -S) 4 ] through a dehydrochlorination−dimerization process (Scheme ). In addition, it has also been found that the Ir−Mo cluster [(Cp*Ir) 2 {Mo(O)Cl 2 }{MoCl 2 (DMF)}(μ 3 -S) 4 ] can be obtained from [Cp*IrCl(μ-SH) 2 IrCp*Cl] and [MoO(DMF) 3 (μ-S) 2 MoO(DMF) 3 ] 2+ through condensation and concomitant dehydration, which is also shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers we have reported that dinuclear complexes containing both bridging and terminal sulfido ligands, [{M(S)(S 2 CNEt 2 )} 2 (μ 2 -S) 2 ] (M = Mo, W), are promising precursors to heterobimetallic clusters with M 2 M‘(μ 3 -S)(μ 2 -S) 3 and M 2 M‘ 2 (μ 3 -S) 4 cores (M‘ = Pd, Pt, Rh, Ir, Ru). The hydrosulfido-bridged dinuclear complexes [(Cp*MCl) 2 (μ 2 -SH) 2 ] (M = Rh, Ir, Ru; Cp* = η 5 -C 5 Me 5 ) and [{(η 6 - p -Pr i C 6 H 4 Me)RuCl} 2 (μ 2 -SH) 2 ] have also been shown to serve as excellent starting compounds for the synthesis of the cubane-type M 4 (μ 3 -S) 4 (M = Ir, Rh, Ru) clusters by in situ generation of the coordinatively unsaturated sulfido-bridged dinuclear species {M 2 (μ 2 -S) 2 } through the loss of HCl, followed by dimerization. It is noteworthy that this method can be extended, for example, to the condensation of the heterobimetallic hydrosulfido-bridged complex [Cp 2 Ti(μ-SH) 2 RuCp*Cl], forming [(CpTi) 2 (Cp*Ru) 2 (μ 3 -S) 4 ] with concomitant loss of HCl and CpH, and crossed condensation between this dinuclear Ti−Ru complex and [(Cp*RuCl) 2 (μ 2 -SH) 2 ] to give [(CpTi)(Cp*Ru) 3 (μ 3 -S) 4 ] …”
Section: Introductionmentioning
confidence: 99%
“…Mixed-metal sulfido clusters have attracted attention in the past decade, because of possible bimetallic synergistic effects 11 in certain types of heterogeneous metal sulfide catalysts. Adduct formation of hydrosulfido complexes with heterometal complexes is a practical route to mixed-metal hydrosulfido-bridged complexes. 10c, …”
Section: Introductionmentioning
confidence: 99%